Bioactive acridone alkaloids and their derivatives from Citrus aurantium (Rutaceae). (February 2019) - Bissim, Samuel Magloire; Kenmogne, Sidonie Béatrice; Tcho, Alain Tadjong; Lateef, Mehreen; Ahmed, Ayaz; Ngeufa Happi, Emmanuel; Wansi, Jean Duplex; Ali, Muhammad Shaiq; Kamdem Waffo, Alain François
Graphical abstract: Highlights: Citrus aurantium is widely used as traditional medicine, food and cosmetic industry. A new seco tirucallane, was isolated from the differents parts of C. aurantium Acetylation of acridones provided the hitherto not reported monoacetyl derivatives. Significant cytotoxicity activity was recorded against human cancer cell lines with IC50 of 32.33 and 44.52 μg/mL. Abstract: Phytochemical studies on Citrus aurantium led to the isolation and characterization of a new seco tirucallane, namely 1 β -hydroxy-3, 4-secotirucalla-4(28)-7, 24-trien-3, 21-dioic acid (1), together with the previously reported compounds citracridone I (2 ), citruisinine II (3 ), citracridone II (4 ), 5-hydroxynoracronycine (5 ), citpressine II (6 ), citpressine I (7 ), buntamine (8 ), 8-hydroxy-6-methoxy-3-pentylisocoumarin (9 ), xanthyletin (10 ), clausarin (11 ), ( E )-suberenol (12 ), transgleinadiene (13 ), methoxysuberenol (14 ), fridelin (15 ), lupeol (16 ), limonin (17 ), a mixture of stigmasterol and β -sitosterol (18 ) and β -sitosterol-3- O - β -d -glucoside (19 ). The structures of these compounds were determined by comprehensive spectroscopic analyses of 1D and 2D NMR and EI- and ESI-MS and comparison with the reported data. Above compounds are reported here from this species for the first time. In addition, acetylation of citracridone I (2 ) and citruisinine II (3) provided the hitherto not reported monoacetyl derivatives2a and3a, respectively. Crude extracts, isolated compounds and derivatives were submitted to bioassays. While compound3 showed significant antioxidant activity with IC50 of 45.5 μM, comparable to the positive control BHA with 44.2 μM, compounds2a, 4 and5 were significantly active in the urease inhibition assay with IC50 s of 28.5, 25.5 and 29.9 μM comparable to the positive control Thiourea with 21.6 μM. Moreover, moderate to weak cytotoxicity activity was recorded for all tested compound against human large cell lung cancer cell line NCI-H460 and human squamous carcinoma cell line CAL-27 with IC50 of 32.33 and 44.52 μg/mL, respectively, compared to Cisplatin and 5-Flurouracil displaying 19.00 and 17.79 μg/mL, respectively.